Jurisdictional Dualism and Military Accountability: Challenges of Human Rights Enforcement in Indonesia’s Security Sector - Muhammad Arbani (Jurnal Syntax Transformation, 2025)
This article critically examines the dual judicial system in Indonesia that governs the prosecution of gross human rights violations involving members of the Indonesian National Armed Forces (TNI). While the Human Rights Court has the legal authority to try serious violations, the concurrent jurisdiction of military courts over active military personnel creates significant barriers to accountability and justice. This legal dualism fosters impunity and weakens public trust in Indonesia’s justice system. The article analyzes key cases, institutional dynamics, and the political legacy that perpetuate this impunity, alongside the expanded role of the military in internal security. It argues that comprehensive legal and institutional reforms, coupled with strong political will, are essential to harmonize jurisdiction, strengthen civilian oversight, and ensure equality before the law. Such reforms are critical for Indonesia to reconcile national security with human rights protections and to consolidate its democratic governance.